Dip-Coating Methods for Carbon Membrane Fabrication: Effects of Coating-Carbonization-Cycles on Hydrogen Separation Prepared from P84/NCC - Norazlianie, Sazali; Mohd Syafiq, Sharip; Haziqatulhanis, Ibrahim; Ahmad Shahir, Jamaludin; Wan Norharyati, Wan Salleh (SpringerLink, 2019)
In this paper depicts the manufacture and assessment of tubular carbon membrane equipped from BTDA-TDI/MDI (P-84) polyimide mixes with Nanocrystalline cellulose (NCC). Given earlier investigations, we planned the theory that tubular carbon membrane performance could impose constraints by controlling the carbonization conditions which directed with a heating rate of 3 ℃/min, a final temperature of 800 ℃ and stabilization temperature of 300 ℃. The principal purpose of this examination is to acquaint successful dip-coating strategies with produce superior tubular carbon membrane. The coating-carbonization cycles (1, 2, 3, and 4 times) have been considered. This methodology empowers quick and straightforward assessment of dip-coating techniques to yields high separation performance. Gas separation performance of the carbon membranes was adequately carried out by a single gas permeation experiment of H2, and N2 to explore the transport component in the carbon membrane separation process. In this case, the most elevated selectivity of 434.68 ± 1.39 for H2/N2; side by side with H2 permeance of 1399.66 ± 5.22 GPU shall accomplish by employing two coating-carbonization-cycles.